Proceedings of the 7th International Conference on Autonomic Computing 2010
DOI: 10.1145/1809049.1809052
|View full text |Cite
|
Sign up to set email alerts
|

Efficient resource provisioning in compute clouds via VM multiplexing

Abstract: Resource provisioning in compute clouds often requires an estimate of the capacity needs of Virtual Machines (VMs). The estimated VM size is the basis for allocating resources commensurate with demand. In contrast to the traditional practice of estimating the size of VMs individually, we propose a joint-VM provisioning approach in which multiple VMs are consolidated and provisioned together, based on an estimate of their aggregate capacity needs. This new approach exploits statistical multiplexing among the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
199
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(202 citation statements)
references
References 28 publications
(28 reference statements)
0
199
0
3
Order By: Relevance
“…Various workload analysis demonstrated that 30~50% (and sometimes up to 90%) of server memory capacity goes unused [52][53][54][55]. Many of these scenarios indicated that CPU capacity is exhausted before memory capacity is reached, therefore leaving a fraction of the memory unused.…”
Section: Rack Scale Composable Memorymentioning
confidence: 99%
“…Various workload analysis demonstrated that 30~50% (and sometimes up to 90%) of server memory capacity goes unused [52][53][54][55]. Many of these scenarios indicated that CPU capacity is exhausted before memory capacity is reached, therefore leaving a fraction of the memory unused.…”
Section: Rack Scale Composable Memorymentioning
confidence: 99%
“…Authors in [27] present a control-oriented model that considers cyber and physical dynamics in datacenters to study the potential impact of coordinating the IT and cooling controls. To achieve further power savings while maintaining the QoS level, joint relationships among VMs, like load correlations, have been exploited in recent works [36,24,19]. For instance, in [24], Meng et al proposed a VM sizing technique that pairs two uncorrelated VMs into a super-VM by predicting the workloads.…”
Section: Related Workmentioning
confidence: 99%
“…The most widely used traces are World Cup web site workloads that date back to 1998 [Arlitt and Jin, 2000;Petrucci et al, 2011], or are derived from the TPC-W benchmark [Singh et al, 2010], which was last updated in 2001. In contrast to conventional approaches, we seek an alternative to generate the workload -converting the CPU utilization traces of an existing production system into the workload input of a discrete simulator [Verma et al, 2007;Chen et al, 2005;Meng et al, 2010]. According to the basic utilization law [Kleinrock, 1975], the utilization multiplied by a normalized constant is essentially the request rate, especially when the load is below 100% utilization.…”
Section: ë ñùð ø óò ïóö ðómentioning
confidence: 99%
“…Following approaches used in [Verma et al, 2007;Chen et al, 2005;Meng et al, 2010], we adopt the utilization traces from current IBM production systems as workload input for each service, i.e., to generate the invocation requests. Based on the basic utilization law [Kleinrock, 1975], the utilization multiplied by a normalized constant reflects the request rate, especially when the load is below 100% utilization.…”
Section: º¿º¾ ì ïóö ðó × áòúó ø óò ê õù ×ø×mentioning
confidence: 99%